2015
DOI: 10.1002/ajoc.201500189
|View full text |Cite
|
Sign up to set email alerts
|

Alumina‐Supported Copper Iodide: An Efficient and Recyclable Catalyst for Microwave‐Assisted Synthesis of 1,4‐Disubstituted 1,2,3‐Triazoles via Three‐Component Reaction in Water

Abstract: Ao ne-pot procedure fort he synthesis of 1,4-disubstituted 1,2,3-triazoles by at hree-component reactiono f allyl or benzyl halides, sodiuma zide, and terminal alkynes over an eutral alumina-supported copper iodide catalyst has been developed. The products were isolated by simple filtration followed by washing of the catalystw ith acetone. The products were obtained in almost pure form in up to 98 % yield (TON 495). The catalystc an be recycled for more than eight subsequent reactions. The halides are directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…Recently, copper has been immobilized on various supports for the synthesis of triazole derivatives . Agalave et al [15a].…”
Section: Introductioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Recently, copper has been immobilized on various supports for the synthesis of triazole derivatives . Agalave et al [15a].…”
Section: Introductioncontrasting
confidence: 59%
“…Recently, copper has been immobilized on various supports for the synthesis of triazole derivatives . Agalave et al [15a]. supported copper iodide on alumina and used it for the synthesis of 1,2,3‐triazole derivatives using microwave irradiation in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although details of the preparation and structure are not entirely clear, Agalave et al reported the use of CuI on bare neutral alumina as a cost-effective supported CuAAC catalyst [131]. The material was used in the reactions of activated halides (Scheme 2a) or a few preformed azides (Scheme 1), in water or DMF-water (4:1) with microwave (MW) or ultrasound (US) irradiation.…”
Section: Cu Cu2o Cuo and Cux Nanoparticles And Nanocompositesmentioning
confidence: 99%
“…Recently reported catalysts for click reactions with high TOF include, dendrimer nanoreactor for part‐per‐million Cu 1 catalyst (TON =510000, TOF=21200 h −1 ), amphiphilic Cu 1 catalyst (TON=86000, TOF 3600 h −1 ) for two component click reaction and alumina supported CuI (TON=495, TOF=4950 h −1 ) for three component click reactions. The TOF and TON values obtained with our catalyst for both two‐component (Table ) and three‐component reactions (Table , Table S6 and Table S7) are comparable and even higher than the recently reported values…”
Section: Resultsmentioning
confidence: 99%